Antiproliferative and Apoptotic Induction of Allicin in Human Lung Cancer Cell Lines - Hussain, Zeenath Vadakkenchery Mohammed; Sivanandhan, Santhy Kumaran (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The study relied on exploring the anticancer effects of allicin and the experimental parameters to scientifically prove its potential as a natural anticancer agent, condiment and dietary supplement present in several Allium plant varieties. Materials and Methods: In the current investigation, the efficiency of allicin was checked for its antiproliferative and apoptosis-prompting potential in the human lung cancer cell lines A549. Results: The inhibitory concentration (IC50) of allicin was 28μM against A549 cell lines. Marked apoptotic morphological changes and DNA damage were observed and visualized by standard staining. Effects of allicin on the cell cycle were determined using flow cytometry. Allicin induced apoptosis of A549 cells 24 h after treatment and decreased the number of in S-phase and indicating cell cycle arrest at G1. These results suggest that allicin killed cancer cells through apoptosis and cell cycle arrest. Further, protein and gene expressions were analyzed by western blot and RT-PCR analysis. Our results showed that, the allicin instigated apoptotic cell death in through intrinsic pathways by the activation of Caspase family proteins.
Keywords: Allicin; Cytotoxicity; Lung cancer; Apoptosis; Protein expression